2016
DOI: 10.1039/c6fo00042h
|View full text |Cite
|
Sign up to set email alerts
|

Separation and purification of an anti-tumor peptide from rapeseed (Brassica campestris L.) and the effect on cell apoptosis

Abstract: Rapeseed peptides were prepared by means of the combined methods of the laboratory bacteria enzyme synergy and the solid-state fermentation of rapeseed meal. The rapeseed peptides were separated and purified with the tumor cell in vitro anti-proliferative activity as an index. Moreover, a kind of rapeseed peptide component RSP-4-3-3 (rapeseed anti-tumor peptide RSP-4-3-3) with high activity was selected. Furthermore, by using reversed-phase high performance liquid chromatography (RP-HPLC) coupled with electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Also, Wang et al. (2016) from Brassica campestris identified a peptide (WTP), of 408.2 Da that at a concentration of 1.6 mg/ml and 72 hr of treatment, was able to reduce cell viability of HepG2 by 36.97 ± 4.06%. On the HepG2 cell line, the percentage of inhibition reported by the <1 kDa fraction is higher than those reported by the single identified peptides discussed above; these differences in activity could be attributed to the characteristics of the peptides that compose the protein fraction, such as their amino acid composition, length, net charge, and structural conformation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Wang et al. (2016) from Brassica campestris identified a peptide (WTP), of 408.2 Da that at a concentration of 1.6 mg/ml and 72 hr of treatment, was able to reduce cell viability of HepG2 by 36.97 ± 4.06%. On the HepG2 cell line, the percentage of inhibition reported by the <1 kDa fraction is higher than those reported by the single identified peptides discussed above; these differences in activity could be attributed to the characteristics of the peptides that compose the protein fraction, such as their amino acid composition, length, net charge, and structural conformation.…”
Section: Resultsmentioning
confidence: 99%
“…L. Wang et al. (2016) reported the separation and purification of a protein fraction with a molecular weight of 0.408 kDa from Brassica campestris , which induced apoptosis on the HepG‐2 cancer cell line. Luna‐Vital et al.…”
Section: Introductionmentioning
confidence: 99%
“…Immunomodulatory peptides have attracted much attention because they can enhance the immunity of organisms, stimulate the proliferation of lymphocytes, increase the phagocytic activity of macrophages as well as defense against pathogens in organisms, promote the antibody production and regulate the transformation of T and B cells, and stimulate the secret of cytokine and immunoglobulin (Mallet et al, 2017 ). Recently, various bioactive peptides derived from enzymatic hydrolysis of soybean (Mallet et al, 2017 ), chickpea (Xue et al, 2015 ), rapeseed (Wang et al, 2016 ), wheat (Kawaguchi et al, 2017 ), rice (Taniguchi et al, 2017 ) has been shown interesting immunomodulatory ability.…”
Section: Introductionmentioning
confidence: 99%
“…However, another anti-apoptotic protein Bcl-2 has a function to reduce cytochrome c release, which can be suppressed by p53 [38]. The peptides from rapeseed can up-regulate p53 and Bax but down-regulate Bcl-2 expression in HepG2 cells, while rice protein hydrolysates can induce H9c2 myocardiocytes apoptosis through the Bcl-2/Bax pathway [39,40]. More importantly, a previous study demonstrating a short-term cooperation of 3,4-dihydroxy-trans-stilbene and exogenous Cu also showed preferential apoptosis induction of HepG2 cells via mitochondria apoptosis pathway [41].…”
Section: Discussionmentioning
confidence: 99%